The altering eye : contemporary international cinema (2009)
The Altering Eye is a book about the most fertile period of filmmaking in the mid-twentieth century. This was a period of rediscovering cinema, of returning to zero (as Jean-Luc Godard proclaimed) and advancing beyond the conventions of the Hollywood style. Not merely advancing, but revolting against it. On the level of form and with a vital, largely left-wing political force, filmmakers worldwide explored their art, pushed its limits, made it articulate, eloquent and complex. Audiences responded in kind, their curiosity and desire meeting the imagination of filmmakers to form a nourishing film culture. While writing the book, there was every indication that the cinematic phenomenon I was discussing was an ongoing process. But just before publication, two of the major filmmakers discussed in the book died: the Brazilian Glauber Rocha in 1981 and Rainer Werner Fassbinder in 1982. Their deaths seemed to signal, or at least occur simultaneously with, an equally premature demise of the very film culture that swept across the world from the end of WW II until that decadal moment. The New German Cinema, the last movement in the wave that began with Italian neorealism blew itself out. Its most talented member was dead. Werner Herzog and Wim Wenders seemed to drift off into less creative spaces, though Herzog has found his footing in a number of amazing documentaries. In France, François Truffaut, a founder of the New Wave, died in 1983. Godard, after having brought about the second seismic change in film after Italian neorealism, went into a kind of exile and returned no longer as a perpetrator of a new cinematic vision, but as a narcissist of form. (He may have been this all along, but the formal experimentation he carried on in the 1960s pressed forward on cinema worldwide and changed it; once changed, Godard himself was changed—by the very cinema he helped create.)